2022
DOI: 10.1136/bjsports-2022-105448
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for postoperative surgical site infections after anterior cruciate ligament reconstruction: a systematic review and meta-analysis

Abstract: ObjectivesThe primary aim was to evaluate risk factors for surgical site infections after anterior cruciate ligament reconstruction (ACLR). The secondary aim was to investigate the surgical site infection incidence rate and the mean time to postoperative surgical site infection symptoms.DesignSystematic review and meta-analysis.Data sourcesPubMed, Embase and Web of Science were searched from database inception to September 2021 and updated in April 2022.Eligibility criteriaQuantitative, original studies report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 87 publications
0
9
0
Order By: Relevance
“…A history of superficial infection at 2 weeks postoperatively along with the increased inflammatory markers, swelling, and the MRI findings suspicious of a pericondylar abscess led to a diagnosis of deep infection. Although a higher risk of SSI has been observed in the hamstring tendon grafts than in bone-patellar tendon-bone grafts 1,2 , deep infection was not initially suspected in this case because infection at the femoral side after ACL reconstruction is rare 16 . To the best of our knowledge, there have been no reports on tunnel widening and implant intratunnel migration because of deep infection.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…A history of superficial infection at 2 weeks postoperatively along with the increased inflammatory markers, swelling, and the MRI findings suspicious of a pericondylar abscess led to a diagnosis of deep infection. Although a higher risk of SSI has been observed in the hamstring tendon grafts than in bone-patellar tendon-bone grafts 1,2 , deep infection was not initially suspected in this case because infection at the femoral side after ACL reconstruction is rare 16 . To the best of our knowledge, there have been no reports on tunnel widening and implant intratunnel migration because of deep infection.…”
Section: Discussionmentioning
confidence: 79%
“…Previous studies have reported several risk factors of infection after ACL reconstruction 2,16 . One thing to note is that atopic dermatitis may be a risk factor because patients are susceptible to S. aureus colonization 22,23 .…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…It was therefore decided to proceed with hematoma evacuation, debridement including removal of all foreign material such as sutures, and lavage. Infection was ruled out before performing a reconstruction procedure using an allograft because elevated infection rates have been reported for tendon reconstructions using allografts or autografts in comparison with tendon repairs [11][12][13] . Various types of reconstruction have been proposed for defects that cannot be approached with primary repair because of defect size, retraction of tendon stumps that precludes adequate reapproximation, or poor tendon quality [14][15][16][17][18] .…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that initiating intensive glycemic control for 24 h after gynecologic oncology surgery in EC patients with diabetes or postoperative blood sugar significantly lowers the SSI rate 27,28 . It has been determined that increased BMI (≥30 kg/cm 2 ) was identified to be an independent risk factor for SSI when patients undergoing general, orthopaedic and gynaecological surgery 16,24,29–32 . Emerging data have demonstrated a correlation between BMI and the risk of SSI in EC patients 9,33 .…”
Section: Discussionmentioning
confidence: 99%